Open and distance learning (ODL) prospects and challenges the case of University of Zamboanga - Knuttel, Sven Heinrich B. (2013)
Abstract:
Research study is about prospects and challenges of open and distance learning (ODL), which is a way of combining work and family responsibilities with educational opportunities, in Universidad de Zamboanga (UZ). Presented in this study is the mode, Learning management system (LMS), readiness of the faculty, and infrastructure/facilities to consider for ODL.
Descriptive-qualitative method was used. Data gathering was done at Universidad de Zamboanga: City Campus, J.S. Alano Street and Main Campus, Don Toribio Street Tetuan, Zamboanga City; MSU-IIT, Iligan City; and UPOU, Los Baños, Laguna. Data gathering was primarily through schedule interview for the curriculum specialist, key informants, and questionnaire for instructors of UZ. Treatment of data was done through coding and documents analysis.
As shown in the study the mode suited for ODL is blended learning. The LMS are moodle, Google apps for education and blackboard with UZ's faculty readiness with 70.5%. A number of robust internet service providers (ISP), server hosting, backup power & backup servers, and module developers should be the focus of infrastructure of ODL.
The mode of ODL suited for the UZ is blended learning. Combination of google apps for education and Moodle is recommended for LMS. Intense trainings, workshops and seminars on ODL for the teachers are also suggested by the researcher.

Executive Summary:
Open learning and distance education refers to approaches to learning that focus on freeing learners from constraints of time and place while offering a flexible learning opportunities. For many students, open and distance learning (ODL) is a way of combining work and family responsibilities with educational opportunities. Distance education and distance learning is a field of education that focuses on teaching methods and technology with the aim of delivering teaching. Often on an individual basis, to students who are not physically present in an traditional educational setting such as a classroom. It's been described as a "process to create and provide access to learning when the source of information and the learners are separated by the and distance, or both" (Honeyman & Miller, 1993). The open nature of distance learning might be formally nstitutionalized in such policies as open admissions, and freedom of selection of what, when and where to learn. The openness of distance learning is also seen in relatively flexible organizational structures, delivery and communication patterns as well as the use of various technologies to support learning (UNESCO, 2006).
There is a need to move the world in the right direction. Open and distance learning (ODL), online learning, and open educational resources (OER) can help, and increasingly popular. Technology and the Internet have - coupled with demand - kick started a long term development that is impossible to stop. But to distil the real added value from ODL, online learning and OER is not a quick win. It takes competence, capacity, leadership, cross sectoral cooperation, and partnerships (Titlestand, 2012).

Technology in our world today is vastly growing n an incredible rate and institutions are trying to keep up with the fast phase. In the Philippines, education is very critical especially if are considered to be one of the over populated counties in the world to date. Thanks to new technologies, open and distance learning can reach a larger space. The non-traditional way of teaching and learning will become more various corresponding to the needs of learners. Furthermore, non-traditional education is the new method of learning and teaching in our generation and generations to come.
Keywords: Distance education; Online learning; Open and distance eLearning